Mapping EST-derived SSRs and ESTs involved in resistance to bacterial blight in Manihot esculenta - López, C.E.; Quesada Ocampo, LM; Bohórquez Cháux, Adriana; Duque E., Myriam Cristina; Vargas Daza, Jaime; Tohme, Joseph M.; Verdier, Valerie M. (Canadian Science Publishing, 2007)
Cassava (Manihot esculenta Crantz) is a major root crop widely grown in the tropics. Cassava bacterial blight, caused by Xanthomonas axonopodis pv. manihotis (Xam), is an important disease in Latin America and Africa resulting in significant losses. The preferred control method is the use of resistant genotypes. Mapping expressed sequence tags (ESTs) and determining their co-localization with quantitative trait loci (QTLs) may give additional evidence of the role of the corresponding genes in resistance or defense. Twenty-one EST-derived simple sequence repeats (SSRs) were mapped in 16 linkage groups. ESTs showing similarities with candidate resistance genes or defense genes were also mapped using strategies such as restriction fragment length polymorphisms, cleaved amplified polymorphic sequences, and allele-specific primers. In total, 10 defense-related genes and 2 bacterial artificial chromosomes (BACs) containing resistance gene candidates (RGCs) were mapped in 11 linkage groups. Two new QTLs associated with resistance to Xam strains CIO121 and CIO151 were detected in linkage groups A and U, respectively. The QTL in linkage group U explained 61.6% of the phenotypic variance and was associated with an RGC-containing BAC. No correlation was found between the new EST-derived SSRs or other mapped ESTs and the new or previously reported QTLs.